Holocene slip rate along the Gyaring Co Fault, central Tibet. Issue 16 (20th August 2014) - Shi, Xuhua; Kirby, Eric; Lu, Haijian; Robinson, Ruth; Furlong, Kevin P.; Wang, Erchie
Abstract Although geodetic measurements of interseismic deformation in interior Tibet suggest slow strain accumulation, active slip along the right‐lateral Gyaring Co Fault is suggested to be between 8 and 21 mm/yr. Reliable geologic constraints on the slip rate along this fault are sparse. Here we document 12 ± 2 m of right‐lateral displacement of lacustrine shorelines across the Gyaring Co Fault. Optically stimulated luminescence ages of the shorelines are tightly clustered between 4.1 and 4.4 ka. These data require an average slip rate of 2.2–3.2 mm/yr along the central Gyaring Co Fault during the latter half of the Holocene. Consideration of seismic cycle effects allows the possibility of slightly higher average slip rates, up to 2.2–4.5 mm/yr. Overall, our results suggest that the slip rate along the Gyaring Co Fault is similar to other strike‐slip faults in interior Tibet, supporting the notion that active deformation in this region is distributed among numerous, slowly moving faults.